Determining the strained state of prefabricated metal corrugated structures of a tunnel overpass exposed to the dynamic loading from railroad rolling stock - Kovalchuk, Vitalii; Koval, Maksym; Onyshchenko, Artur; Kravets, Ivan; Bal, Olena; Markul, Ruslan; Vikhot, Svitlana; Petrenko, Oleksiy; Rybak, Roman; Milyanych, Andriy (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports the analysis of prospects for the use of prefabricated metal corrugated structures in the body of the embankment of a railroad track in the form of a tunnel overpass in order to pass road vehicles and railroad rolling stock. A technique of inertial dynamic tests of the deformed state of a tunnel overpass from prefabricated metal corrugated structures during the passage of railroad rolling stock is given, by measuring accelerations at the top and on the sides of overpass structures. An algorithm is proposed for processing the acceleration signal for assessing the strained state of metal corrugated structures of a tunnel overpass under the action of dynamic load from railroad transport. Experimental dynamic measurements of accelerations arising at the top and on the sides of a tunnel overpass during the passage of passenger and freight railroad rolling stock were carried out. The maximum value of accelerations arising at the top of a tunnel overpass during the passage of a freight train was 7.99 m/s2, and when passing a passenger train – 6.21 m/s2; the maximum accelerations that occur on the sides were 2.63 m/s2 and 1.77 m/s2. It is established that the maximum deformations of metal corrugated structures of the top of a tunnel overpass, when passing freight and passenger trains are, respectively, 1.63 mm and 1.11 mm. The maximum strains of metal corrugated structures on the sides of an overpass are 1.07 mm and 0.48 mm. The value of relative deformations in the vertical and horizontal dimensions of the structures of a tunnel overpass under the action of dynamic loads from the railroad rolling stock has been found. The relative vertical strains of an overpass amounted to 0.020 %; horizontal – 0.012 %. The practical significance of this work is that with the help of the devised procedure for measuring accelerations, it is possible to assess the strained state of metal corrugated structures under the influence of dynamic loads from the railroad rolling stock